2010
DOI: 10.1590/s0066-782x2010005000125
|View full text |Cite
|
Sign up to set email alerts
|

Relação entre depressão, nível de BNP e comprometimento ventricular na insuficiência cardíaca

Abstract: Background: Depression is a common comorbidity in heart failure (HF); however, the mechanisms related to a poorer outcome of depressed patients with HF remain unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
1
4
0
1
Order By: Relevance
“…Similar to the findings of our study, significantly lower BDNF levels are observed in patients with major depressive disorder compared to the control group 35. In contrast to our findings, in patients with heart failure, BDNF levels were reported to be higher in depressive patients compared to the patients without depression 3638…”
Section: Discussionsupporting
confidence: 88%
“…Similar to the findings of our study, significantly lower BDNF levels are observed in patients with major depressive disorder compared to the control group 35. In contrast to our findings, in patients with heart failure, BDNF levels were reported to be higher in depressive patients compared to the patients without depression 3638…”
Section: Discussionsupporting
confidence: 88%
“…[102021] In elderly patients with type 2 diabetes, a relatively weak association between NT-proBNP levels and depressive symptoms assessed on the Hospital Anxiety and Depression Scale (HADS) has been observed. [12] In patients with heart failure, individuals underwent depression assessment using the 17-item version Hamilton Depression Scale, and the results revealed that patients with severe depression showed a higher degree of BNP stimulation,[20] which was consistent with the results. Of interest, the plasma concentrations of NT-proBNP were positively correlated with the severity of depression in unmedicated patients with MDD.…”
Section: Discussionmentioning
confidence: 99%
“…[26] Aguiar et al . [20] showed that heart failure patients with severe depression presented higher BNP levels but less cardiac impairment than those without depression or with mild and moderate depression. As mentioned in the introduction, depression is a risk factor for morbidity and mortality in AMI patients; even existing depressive symptoms will have an adverse impact on the cardiovascular prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…The association of BNP with left ventricular diastolic function appears to be particularly strong in individuals with DM (7). Other studies indicated that BNP was not only associated with left ventricular abnormalities but also with cardiovascular disease and mortality risk in DM patients (8,9). Therefore, when BNP is used to assess cardiovascular disease (CVD) risk in CHF patients, the presence or absence of DM should be taken into account (10,11).…”
Section: Introductionmentioning
confidence: 95%